The three-step theory of suicide: Description, evidence, and some useful points of clarification - Klonsky, E. David; Pachkowski, Mikayla C.; Shahnaz, Arezoo; May, Alexis M. (Preventive medicine, 2021)
There has been considerable uptake of the Three-Step Theory (3ST) of suicide since its publication in 2015. The 3ST is a concise, evidence-based, and actionable theory that explains suicide in terms of four factors: pain, hopelessness, connection, and capability for suicide. The 3ST has not only been cited in hundreds of scientific papers, but incorporated into continuing education programs, gatekeeper training, and self-help resources. In this context, it is useful to clarify the theory's content and review its scientific support. Thus, the present article describes the 3ST, provides an updated evidence review for each of its premises, and offers several points of clarification so that the claims of the 3ST may be better understood, evaluated, and applied. To date, research (including research on correlates, risk factors, motivations, warning signs, and means-safety interventions) supports the 3ST. At the same time, there are aspects of the theory that are challenging to operationalize and that require further testing. •The Three-Step Theory (3ST) is a concise and actionable theory of suicide.•The 3ST focuses on four factors: pain, hopelessness, connection, suicide capability.•Studies on correlates, risk factors, motivations, and warning signs support the 3ST.•This article clarifies the 3ST so it may be better understood, tested, and applied.•Aspects of the 3ST remain challenging to operationalize and test.